2011
DOI: 10.1002/ar.21516
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of the Autonomic Cranial Ganglia: An Immunohistochemical Study of Mid‐Term Human Fetuses

Abstract: The cranial parasympathetic ganglia have been reported to paradoxically contain the sympathetic nerve marker, tyrosine hydroxylase (TH), in addition to neurons expressing parasympathetic markers such as vasoactive intestinal peptide (VIP) and neuronal nitric oxide synthase (nNOS). However, the distribution of these molecules in the cranial ganglia of human fetuses has not yet been examined. Using paraffin sections from 10 mid-term human fetuses (12-15 weeks), we performed immunohistochemistry for TH, VIP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“… (A) Adult TH-expressing DRG neurons have been detected in a number of species, including rat, guinea pig and mouse (—, not determined; * in humans, only embryonic expression has so far been studied [43]). (B) TH-expressing mouse DRG neurons are primarily small and medium-sized.…”
Section: Figurementioning
confidence: 99%
“… (A) Adult TH-expressing DRG neurons have been detected in a number of species, including rat, guinea pig and mouse (—, not determined; * in humans, only embryonic expression has so far been studied [43]). (B) TH-expressing mouse DRG neurons are primarily small and medium-sized.…”
Section: Figurementioning
confidence: 99%
“…Several reports have documented the paradoxical presence of both sympathetic and parasympathetic nerve markers in the human nervous system, although rather than nNOS, vasoactive intestinal peptide (VIP) has been used as a parasympathetic nerve marker: e.g. VIP-positive neurons in the prevertebral sympathetic ganglia [17]; TH-positive neurons in the ciliary parasympathetic ganglion [8,18], in the submandibular parasympathetic ganglion [18], and in the parasympathetic pelvic ganglia [2,3]. The intrapharyngeal ganglion of the cat near the palatine tonsil carries not only abundant VIP-positive neurons but also a few TH-positive neurons [10].…”
Section: Discussionmentioning
confidence: 99%
“…TH is a rate-limiting enzyme of catecholamine synthesis in sympathetic ganglion cells, whereas nNOS is a key enzyme in the production of nitric oxide, a molecule that directly regulates vasorelaxation and blood supply, and a well-known marker of parasympathetic neurons. In humans, nNOS reactivity has been investigated particularly in the pelvic nerves [6,7] but previous descriptions for the head region have been limited to the cranial ganglia of the autonomic nervous system [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in the V2 and V3 of cats, Hoffmann and Matthews () reported that sensory fibers are much greater in number than sympathetic fibers in contrast to the median and ulnar nerves. No or few sympathetic nerve fibers seemed to be transferred in the infratemporal and pterygopalatine fossae from artery‐bounded sympathetic nerves as well as from the nearby ganglia although the human pterygopalatine and otic ganglia contain TH‐positive neurons (Kiyokawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…contrast to the median and ulnar nerves. No or few sympathetic nerve fibers seemed to be transferred in the infratemporal and pterygopalatine fossae from arterybounded sympathetic nerves as well as from the nearby ganglia although the human pterygopalatine and otic ganglia contain TH-positive neurons (Kiyokawa et al, 2012). Kashima et al (2013) reported that the basic taste stimuli elicit regional differences in the facial skin blood flow without simultaneous systemic circulatory changes.…”
Section: Discussionmentioning
confidence: 99%